Assessment of Noise-induced Temporary Threshold Shift in Dentistry Students Following Oral Magnesium Intake - Silva, Isabelle Braz de Oliveira; Garavelli, Sérgio Luiz; Serra, Lucieny Silva Martins; Araújo, Juliana Gusmão de; Sampaio, André Luiz Lopes (Revista JRG de Estudos Acadêmicos, 2025)
Long‐term exposure to sounds ≥85 dB causes noise-induced hearing loss, which can be temporary or permanent, and it can be improved through the use of magnesium. This study aimed to determine whether noise in the dental laboratory negatively affects dental students’ auditory system and whether magnesium ion supplementation prevents hearing loss. Sound pressure levels (SPLs) were monitored during the laboratory class and expressed in logarithmic function. Students attending regular dental practical classes were randomized into two groups: the study group (received 200 mg of magnesium 1 h before the laboratory class) and the control group (received 200 mg placebo at the same time). Distortion product otoacoustic emission (DPOAE) tests were performed before and after noise exposure during the class. The mean SPL equivalent was 75.3 dB; however, SPL peaked at 97.3 dB. DPOAE parameters did not change after approximately 3 h of exposure. There were no significant differences between the groups in all the frequencies studied for the amplitude (p=0.82) and S/N ratio (p=0.08) analyses. A single magnesium supplementation did not produce any side effects; however, no benefit was observed in hearing preservation. Occupational noise and magnesium supplementation did not alter DPOAE results.